(untitled) (Open Herald: Periodical of Methodical Research, 2026)
This article provides a scientific analysis of the content and essence of the concept of law, its role in society, and the main theoretical approaches. It examines the role of law in regulating social relations, as well as its features and functions. Additionally, a comparative analysis of positivist and natural law concepts is presented